Women will vote : winning suffrage in New York State - Goodier, Susan; Pastorello, Karen, 1956- (Three Hills, an imprint of Cornell University Press, 2017)
Women Will Vote celebrates the 2017 centenary of women's right to full suffrage in New York State. Susan Goodier and Karen Pastorello highlight the activism of rural, urban, African American, Jewish, immigrant, and European American women, as well as male suffragists, both upstate and downstate, that led to the positive outcome of the 1917 referendum. Goodier and Pastorello argue that the popular nature of the women's suffrage movement in New York State and the resounding success of the referendum at the polls relaunched suffrage as a national issue. If women had failed to gain the vote in New York, Goodier and Pastorello claim, there is good reason to believe that the passage and ratification of the Nineteenth Amendment would have been delayed. Women Will Vote makes clear how actions of New York's patchwork of suffrage advocates heralded a gigantic political, social, and legal shift in the United States. Readers will discover that although these groups did not always collaborate, by working in their own ways toward the goal of enfranchising women they essentially formed a coalition. Together, they created a diverse social and political movement that did not rely solely on the motivating force of white elites and a leadership based in New York City. Goodier and Pastorello convincingly argue that the agitation and organization that led to New York women's victory in 1917 changed the course of American history.